Peran literasi keuangan syariah dalam membangun persepsi dan kepercayaan nasabah terhadap bank syariah - rohmah, jazilatur (Maliki Interdisciplinary Journal, 2026)
This article aims to develop a conceptual framework that explains how Islamic financial literacy influences perceptions and ultimately shapes customer trust in Islamic banks. Although Islamic banking in Indonesia continues to grow, the reality on the ground shows that public understanding of Islamic finance remains low. Many people are not yet familiar with the principles, characteristics, and workings of Islamic products, giving rise to various misconceptions, such as that Islamic banks are the same as conventional banks or that contracts are merely a formality in Islamic transactions. This lack of understanding can influence how the public views Islamic banks and affect their level of trust.This article is conceptual in nature, using an analytical approach to various literature to understand the relationship between three main aspects, namely literacy, perception, and trust. Literature analysis shows that the higher a person’s Islamic financial literacy, the better their perception of the operations and values applied in Islamic banking. Positive perceptions will then contribute to increased customer confidence in using Islamic banking services. The conceptual framework developed in this article is expected to serve as a basis for further research.